2012
DOI: 10.1016/j.neuroimage.2012.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Development of BOLD signal hemodynamic responses in the human brain

Abstract: In the rodent brain the hemodynamic response to a brief external stimulus changes significantly during development. Analogous changes in human infants would complicate the determination and use of the hemodynamic response function (HRF) for functional magnetic resonance imaging (fMRI) in developing populations. We aimed to characterize HRF in human infants before and after the normal time of birth using rapid sampling of the Blood Oxygen Level Dependent (BOLD) signal. A somatosensory stimulus and an event rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
217
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(237 citation statements)
references
References 95 publications
17
217
1
2
Order By: Relevance
“…41 The nature of the healthy neonatal functional hemodynamic response is still an issue of some debate. While several studies suggest the neonatal (and even early preterm) hemodynamic response is consistent with that observed in the mature brain, 42,43 a recent study in the rat model suggests that the hemodynamic response to an external stimulus varies significantly with postnatal age. 44 In the infant rat, the hemodynamic response was found to consist of a small increase in HbO, followed by increase in HbR, while the response in the adult rat was consistent with the typical adult human response, i.e., an increase in HbO with a concomitant decrease in HbR.…”
Section: Discussionmentioning
confidence: 76%
“…41 The nature of the healthy neonatal functional hemodynamic response is still an issue of some debate. While several studies suggest the neonatal (and even early preterm) hemodynamic response is consistent with that observed in the mature brain, 42,43 a recent study in the rat model suggests that the hemodynamic response to an external stimulus varies significantly with postnatal age. 44 In the infant rat, the hemodynamic response was found to consist of a small increase in HbO, followed by increase in HbR, while the response in the adult rat was consistent with the typical adult human response, i.e., an increase in HbO with a concomitant decrease in HbR.…”
Section: Discussionmentioning
confidence: 76%
“…For example, task-based fMRI and FNIRS studies using passive stimuli have revealed adult-like positive blood-oxygen-level-dependent (BOLD) signals in response to sensorimotor 74, 75 , visual 76 , and auditory stimuli 77, 78 in human newborns and infants. FNIRS studies have documented the emergence and gradual improvement of various other functional responses during spatiotemporal processing 79 , object recognition 80 , learning 81 and social processing 82 , among other processes, during the first year of life.…”
Section: Networkmentioning
confidence: 99%
“…Much of our present-day knowledge about brain-behavior relationships shortly after birth comes from task-based fMRI studies (Allievi et al, 2016;Anderson et al, 2001;Arichi et al, 2013Arichi et al, , 2012Arichi et al, , 2010Born et al, 1996;Dehaene-Lambertz et al, 2010, 2002Erberich et al, 2006;Heep et al, 2009;Konishi et al, 2002;Morita et al, 2000). These studies have provided important background on the brain's responses to sensory input during the earliest phases of development of brain-behavior interactions.…”
Section: Functional Connectivity and Behavioral Counterpartsmentioning
confidence: 99%